THE EFFECT OF ABSORPTIVE CAPACITY ON THE RELATIONSHIP BETWEEN INTELLECTUAL CAPITAL AND SMES PERFORMANCE IN PAKISTAN - Ahmad Imran Khan,; Wan Fadzilah Wan Yusof, (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
The ability to acquire and learn knowledge has been most important challenges faced by business around the word. Especially Small and Medium Enterprises (SMEs). SMEs is a backbone of any emerging economy. The aim of this research is to look at how Absorptive Capacity affects Intellectual Capital and SME efficiency in Pakistan.Partial Least Square (PLS 3.0) with Structural Equational Model (SEM) technique will be used to assess the impact of Intellectual Capital on SMEs performance with a mediating role of Absorptive Capacity in a developing economy like Pakistan. The data will be collected from top managers of SMEs of Pakistan through survey questionnaires with Likert scale items. The findings of the study will show how absorptive capacity will create impact between the relationship of Intellectual capital and performance of Small and Medium Enterprises in a developing country like Pakistan.Thestudy will a contribution to the literature on Intellectual Capital and SME performance of Pakistan and will help managers, practitioners to recognize the importance of exploitation and transformation of knowledge in small firms.